Autophagy-Mediated Clearance of Free Genomic DNA in the Cytoplasm Protects the Growth and Survival of Cancer Cells - Yao, Mengfei; Wu, Yaqian; Cao, Yanan; Liu, Haijing; Ma, Ningning; Chai, Yijie; Zhang, Shuang; Zhang, Hong; Nong, Lin; Liang, Li; Zhang, Bo (Frontiers in Oncology, 2021)
The cGAS (GMP-AMP synthase)-mediated senescence-associated secretory phenotype (SASP) and DNA-induced autophagy (DNA autophagy) have been extensively investigated in recent years. However, cGAS-mediated autophagy has not been elucidated in cancer cells. The described investigation revealed that active DNA autophagy but not SASP activity could be detected in the BT-549 breast cancer cell line with high micronucleus (MN) formation. DNA autophagy was identified as selective autophagy of free genomic DNA in the cytoplasm but not nucleophagy. The genomic DNA in the cytosol could initiate this process by binding to cGAS and usually cooperates with SQSTM1-mediated autophagy of ubiquitinated histones. Cytoplasmic DNA, together with nuclear proteins such as histones, could be derived from DNA replication-induced nuclear damage and MN collapse. The inhibition of DNA autophagy through either chemical inhibitors or genomic silencing of cGAS or SQSTM1 could suppress the growth and survival of cancer cells, and induced DNA damage could increase the sensitivity to these inhibitors. Furthermore, expanded observations of several other kinds of human cancer cells indicated that high relative DNA autophagy or enhancement of DNA damage could also increase or sensitize these cells to inhibition of DNA autophagy.